Effects of Obesity and Short-Term Metformin Treatment on Liver Steatosis in Female Zucker Rats. (29th May 2020) - Hakkak, Reza; Irby, David; Rose, Shannon; Bennuri, Sirish; Spray, Beverly; Korourian, Soheila
Abstract: Objectives: Non-alcoholic fatty liver disease (NAFLD) is the leading cause of liver disease in adolescents in the US and World, and the risk has increased with the rise in obesity. We reported that obesity increases Fatty liver (steatosis) using an obese Zucker rat model. Metformin is an oral anti-hyperglycemic agent approved by the FDA to treat type 2 diabetes (T2D) in adults and children older than 10 years of age. There is insufficient evidence regarding the effects of metformin in pediatric liver steatosis. The objective of this study was to investigate the effects of short-term metformin treatment on liver steatosis and related serum markers for liver damage. Methods: Five week old lean (n = 16) and obese (n = 16) female Zucker rats after one week of acclimation, received AIN-93 G diet for 8 weeks to induce NAFLD. After 8 weeks, lean and obese rats were randomly assigned to the following four groups (8 rats/group): 1) lean without metformin (LC), 2) lean with metformin (LMet), 3) obese without metformin (ObC), and 4) obese with metformin (ObMet). Metformin were mixed with AIN-93 G diet at 1000 mg/kg of diet. Rats were weighed twice per week. All rats were sacrificed 10 weeks post-metformin treatment and serum and livers were collected. Steatosis was semiquantitated as a score of 1 to 4 based upon the relative degree of steatosis within hepatocytes: 1) < 25%, 2) 25–50%, 3) 50–75%, and 4) >75%. Serums were collected to measure the levels of Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT) on a clinical analyzer. Results: Obese rats gained significantly more weight ( P < .001) than lean rats for both control and Metformin treatment groups and there was no significant difference between ObC vs. ObMet group ( P = 0.20). The mean + SD liver steatosis scores for the LC, LMet, ObC and ObMet groups were 0.13 + o.3, 0.13 + o.3, 3.67 + 0.52 and 3.00 + 0.82. The ObMet treated rats had lower ( P < 0.04) liver steatosis than ObC rats. There were no significant differences for the serum ALT and AST levels between groups. However, obesity increased significantly ( P < 0.01) serum AST levels compared to LC but not in the metformin group. Conclusions: In summary, in the obese zucker rat model, short-term metformin treatment decreased liver steatosis but did not impact serum markers of liver steatosis. Funding Sources: Arkansas Children Research Institute/Arkansas Bioscience Institute.